Antimicrobial Activity of the Essential oil from Seed and oleo-gum-resin Ferula assa foetida against Oral Pathogens - Alireza Daneshkazemi; Hengameh Zandi; Abdolrahim Davari; Mahmood vakili; Majid Emtiazi; Reza Lotfi; Seyed Mohammad Reza Masoumi (Tehran University of Medical Sciences, 2019)
Objectives: The objective of this study was to evaluate the antimicrobial activity of the essential oil obtained from oleo-gum-resin and seeds of Ferula assa-foetida. Materials and Methods: Ferula assa-foetida plants were collected from Tabas, Yazd Province, Iran, during summer 2017. Then, essential oils were obtained from its seeds and oleo-gum-resin using hydrodistillation. Gas chromatography-mass spectrometry (GC-MS) test was performed to determine the contents of the essential oils. Four different doses of each oil were prepared (2.5, 5, 10, and 20 μg/ml), and the antimicrobial activity of each dose against four oral bacteria (Streptococcus mutans, Streptococcus sobrinus, Streptococcus sanguis, Streptococcus salivarius, and Lactobacillus rhamnosus) was evaluated using the disk diffusion method. The data were analyzed using analysis of variance (ANOVA) and Kruskal-Wallis test in SPSS 17 software. Results: The GC-MS findings exhibited that the main compounds found in essential oils yielded from the seeds and oleo gum resin were (Z) -1-propenyl sec-butyl disulfide and (E) -1-propenyl sec-butyl disulfide. Ferula assa-foetida plant showed a significant antimicrobial effect (P<0.05). The essential oil from Ferula assa-foetida oleo-gum-resin had significantly stronger antibacterial properties compared to the essential oil from Ferula assa-foetida seeds (P<0.001). Both essential oils showed antibacterial properties similar to that of Chlorhexidine. The growth inhibition zone was significantly dependent on the essential oil concentration for all bacteria (P<0.05). Conclusions: Our study revealed that essential oils from seeds and oleo-gum-resin of Ferula assa-foetida have antimicrobial properties. More laboratory studies are required to reach a definitive conclusion.